Reflection of the Foreign Pedagogical Experience in Scientific Works of J. Laužikas - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 2004)
The article analyses the point of view of J. Laužikas on the new pedagogy of West Europe and the USA in the beginning of 20th cen. The author underlines that J. Laužikas knew well the experience of foreign school, has studied deeply the new pedagogical trends of beginning of 20th cen., theirs theory and practice. The article notes that J. Laužikas approved of the most of principles of the new school: activity, self-dependence, integration, initiative, individual approach, research, and others. The connections between pedagogical ideas of Laužikas and new pedagogy are disclosed. The short analysis of pedagogical reformist movement in the 20th cen. is presented. The article emphasizes the importance of pedagogical ideas of Laužikas to the modern school of Lithuania. This article represents not only scientific pedagogical ideas of J. Laužikas, but talks about the professor’s humanity – his love of children, trying to perceive the child. The professor in his scientific works analyses the problems of humanistic education, pedagogical communication, knowledge of child, educational psychology and others problems.
Keywords: J. Laužikas; pedagogical trends; new pedagogy; humanistic education; pedagogical communication